Risk assessment in the formation of motivational programs aimed at retaining the heads of organizations - E. V. Ivanova; T. V. Bobko; K. V. Ivanova (Вестник университета)
The relevance of the study is determined by the increasing role of risks in the formation of motivation programs aimed at retaining managers of the middle and top levels of organization management. The purpose of the study was to identify risks that arise in the process of implementing motivation programs for managerial personnel. In the study, the following tasks were solved: determining the sources and risk factors; assessing the probability of risks and the level of possible consequences of a risk event; identifying the risks that are most priority for management based on building a risk map; development of ways to reduce risks that reduce the effectiveness of the implementation of motivational programs to retain managers of the organization. The work uses systematic and situational approaches, expert assessment, the survey method and the Delphi method, risk mapping. The developed measures to eliminate risks will allow organizations to prevent reputational and financial losses and analyze the effectiveness of each implemented motivational tool to retain the leaders of the organization.